Redefined Labour Spaces
1 online resource (xxiv, 350 pages)
Keywords: "This book discusses the transformation of labour movements and trade unionism in post-liberalised India. It looks at emerging collectivism, both in formal and informal sectors, and relates it to changing political and industrial relations. Bringing together studies of resistance, struggles and new forms of negotiations from different industries -agriculture, fisheries, brick kiln, plantations, IT, domestic workers, shipbreakers, sex workers, and miners -this book exposes the myths, realities and challenges that the present generation of workers in India face and struggle with. With contributions from leading thinkers in the field, the work deepens the understanding of the current Indian labour spaces, possibilities for contestations and articulations from below. The volume will be useful to students and researchers of labour studies, economics, sociology, development studies and public policy. It will be an invaluable resource to those engaged with industrial relations, trade unions, human rights, social exclusion as well as labour organisations and research institutions. "--Provided by publisher.